PENGARUH KUALITAS PELAYANAN, KUALITAS MAKANAN DAN KEUNGGULAN BERSAING TERHADAP KEPUASAAN KONSUMEN PADA PRODUK MENTAI RICE DI BEKASI - Laisya Putri; Dian Sudiantini, Noval Febiantoro, Rihadhatul Aisy, Tengku Zaky, Wulan Alfia (CV. Adiba Aisha Amira, 2024)
Mentai rice is a typical Japanese food, more commonly known as mentaiko. This research aims to improve service to consumers, increase the quality of food that is more guaranteed and suitable for consumption and has an important role in increasing operational efficiency and market competitiveness in consumer satisfaction with mentai rice products in Bekasi. The research method used was a quantitative approach with a survey of 80 respondents. Data was collected through questionnaires and then analyzed using multiple correlation and multiple linear regression. The research results show that the coefficient of determination (Adjusted R Square) is 0.632, which means that service quality, food quality and competitive advantage contribute 63.2% to mentai rice products.